Prevalence and associated factors of intention of COVID-19 vaccination among healthcare workers in China: application of the Health Belief Model - Yanqiu Yu; Joseph T. F. Lau; Rui She; Xi Chen; Liping Li; Lijuan Li; Xiaojun Chen (Taylor & Francis Group, 2021)
Healthcare workers (HCWs) are at an increased risk of coronavirus disease 2019 (COVID-19) and warrant COVID-19 vaccination to reduce nosocomial infections. This study investigated: (1) the prevalence of behavioral intention of COVID-19 vaccination (BICV) under eight scenarios combining vaccines' effectiveness/safety/cost, plus two general scenarios of free/self-paid vaccination given governmental/hospital recommendations, (2) perceptions involving preferred timing of COVID-19 vaccination and impacts of various attributes on BICV, and (3) factors of BICV based on the Health Belief Model. An anonymous online cross-sectional survey was conducted among 2,254 full-time doctors/nurses in three Chinese provinces during 10/2020-11/2020. The prevalence of BICV was 75.1%/68.0% among nurses/doctors under the most optimum scenario of this study (free/80% effectiveness/rare mild side effects); it dropped to 64.6%/56.5% if it costed 600 Yuan (USD90). Similar prevalence was obtained (72.7%/71.2%) if the vaccination was recommended by the government/hospitals but dropped to <50% if effectiveness was 50% or mild side effects were common; 13.0% preferred to take up COVID-19 vaccination at the soonest (81.8% would wait and see). Scientific proof (completion of phase III clinical trials and approval from health authorities) was rated the highest in its impacts on vaccination decision, followed by vaccines' performance, and then logistics. Multivariable logistic regression analyses showed that perceived severity, perceived barriers, cues to action, and self-efficacy (but neither perceived susceptibility nor perceived barriers) were significantly associated with the two BICV outcomes. The coverage of COVID-19 vaccination would be high only if the vaccines perform well. Health promotion may take the findings into account.